Effectiveness of Eriomin® in managing hyperglycemia and reversal of prediabetes condition: A double-blind, randomized, controlled study - Ribeiro, Carolina B. [UNESP]; Ramos, Fernanda M. [UNESP]; Manthey, John A.; Cesar, Thais B. [UNESP] (Wiley, 2019)
This study evaluated the potential effectiveness of different doses of Eriomin® on hyperglycemia and insulin resistance associated with other metabolic biomarkers in prediabetic individuals. Prediabetes patients (n = 103, 49 ± 10 years) were randomly divided into four parallel groups: (a) Placebo; (b) Eriomin 200 mg; (c) Eriomin 400 mg; and (d) Eriomin 800 mg. Assessment of biochemical, metabolic, inflammatory, hepatic, renal, anthropometric markers, blood pressure, and dietary parameters were performed during 12 weeks of intervention. Treatment with all doses of Eriomin (200, 400, and 800 mg) had similar effects and altered significantly the following variables: blood glucose (−5%), insulin resistance (−7%), glucose intolerance (−7%), glycated hemoglobin (−2%), glucagon (−6.5%), C-peptide (−5%), hsCRP (−12%), interleukin-6 (−13%), TNFα (−11%), lipid peroxidation (−17%), systolic blood pressure (−8%), GLP-1 (+15%), adiponectin (+19%), and antioxidant capacity (+6%). Eriomin or placebo did not influence the anthropometric and dietary variables. Short-term intervention with Eriomin, at doses of 200, 400, or 800 mg/day, benefited glycemic control, reduced systemic inflammation and oxidative stress, and reversed the prediabetic condition in 24% of the evaluated patients.
Keywords: flavonoids; hyperglycemia; insulin resistance; prediabetic state